2005
DOI: 10.1177/154405910508400615
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bacterial Phylotypes in Endodontic Infections

Abstract: Although molecular studies have revealed potential oral pathogens among the phyla Spirochaetes and Deferribacteres, their occurrence in endodontic infections has not been consistently investigated. In this study, we devised a nested PCR-DGGE approach to survey samples from infected root canals for the presence of members of these two phyla, and to examine their diversity. The primers used also amplified DNA from Atopobium species. Eight of 10 cases showed bands representative of the target bacterial groups. DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Furthermore, the most prevalent species in this study, Atopobium rimae is an Actinobacteria. Previous studies reported that species of the genus Atopobium were detected in cases of systemic bacteremia (35,36) and oral infectious disease, as periodontitis (37,38) and persistent periradicular lesions (15,39). The high prevalence of A. rimae in primary endodontic infections as shown here, which is associated with other data indicating a higher frequency of this species in periradicular soft tissues than in root ends (15), provided evidences to suggest this species as an important endodontic pathogen.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the most prevalent species in this study, Atopobium rimae is an Actinobacteria. Previous studies reported that species of the genus Atopobium were detected in cases of systemic bacteremia (35,36) and oral infectious disease, as periodontitis (37,38) and persistent periradicular lesions (15,39). The high prevalence of A. rimae in primary endodontic infections as shown here, which is associated with other data indicating a higher frequency of this species in periradicular soft tissues than in root ends (15), provided evidences to suggest this species as an important endodontic pathogen.…”
Section: Discussionsupporting
confidence: 81%
“…Experimentation with primer annealing temperatures higher than 56°C (to reduce the tolerance of the primers) significantly reduced the amount of amplicon and was therefore not pursued further. There is some evidence to suggest that if the target of a specific primer is present only at low levels or is absent from a sample, then the primer more readily selects other taxa which are less stringently matched (37). Accordingly, the larger proportion of "Synergistetes" sequences (of the total number of sequences) in subjects with periodontitis (61.4%) than in healthy controls (28.1%) may perhaps imply that there was a greater abundance of "Synergistetes" in the cases.…”
Section: Discussionmentioning
confidence: 99%
“…"Synergistetes" are widely distributed in the environment, form part of the normal microbiota of animals (10), and have also been isolated from a variety of sites in humans, including the oral cavity. "Synergistetes" have been detected in subgingival plaque associated with diseased sites in periodontitis patients (7,13,15,(18)(19)(20)29), in root canals and pus from abscesses in patients with endodontic infections (28,31,32,36,37,44), and in dental caries (27,30). Because the description of this candidate phylum is relatively recent, "Synergistetes" taxa have frequently been misidentified.…”
mentioning
confidence: 99%
“…Such studies found unculturable clones of the phyla Spirochaetes and Synergistetes (formerly known as Deferribacteres) in root canals of teeth with apical periodontitis. [51][52][53] Furthermore, the newly identified taxon Dialister was identified to be a frequent member of the endodontic microbiota residing in infected root canals. 48 More recent approaches included the use of pyrosequencing of 16S rRNA genes to profile the endodontic microbiome.…”
Section: Culture-independent Studiesmentioning
confidence: 99%